2010
DOI: 10.1038/labinvest.2009.147
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the IL-22/REG Iα axis in ulcerative colitis

Abstract: The Regenerating gene (REG) Ia protein, a trophic and/or anti-apoptotic factor, is important in the pathophysiology of gastrointestinal inflammation. Interleukin (IL)-22 is a recently identified cytokine that is suggested to have pivotal roles in inflammatory bowel diseases. We therefore investigated the involvement of the IL-22/REG Ia axis and examined the mechanism of regulation of REG Ia expression by IL-22 stimulation in ulcerative colitis (UC) mucosa. Expression of IL-22, IL-22 receptor 1 (IL-22R1), and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 42 publications
3
81
0
Order By: Relevance
“…IL-6 and IL-8 are reported to induce REG Iα mRNA in vitro [18,21,22] and in vivo [39], and IL-11 [23], IL-22 [24], IFN-γ [25], IFN-β [12] and CINC-2β [26] are also reported to induce REG Iα mRNA. IL-6R and gp130 are known as signal transducers of IL-6.…”
Section: Cytokine/chemokine(s) Gene Expression In Msgmentioning
confidence: 96%
“…IL-6 and IL-8 are reported to induce REG Iα mRNA in vitro [18,21,22] and in vivo [39], and IL-11 [23], IL-22 [24], IFN-γ [25], IFN-β [12] and CINC-2β [26] are also reported to induce REG Iα mRNA. IL-6R and gp130 are known as signal transducers of IL-6.…”
Section: Cytokine/chemokine(s) Gene Expression In Msgmentioning
confidence: 96%
“…Of note, IL-22 is a unique cytokine that is produced by Th17 cells or NK cells, but targeted exclusively to IECs in the intestinal mucosa [70]. It has been shown that the IL-22-STAT3 pathway promotes epithelial regeneration through cell proliferation and increased secretion of factors such as RegIIIb, RegIIIc, or S100A9 [71][72][73]. Mizoguchi et al has shown that local production of IL-22 may promote tissue repair in a mice colitis model [74].…”
Section: Mechanism Of Epithelial Repair In Ibdmentioning
confidence: 99%
“…Total RNA was isolated from GI tissues with Trizol reagent (Invitrogen, Carlsbad, CA). Total RNA (4 g) was reverse-transcribed using oligo-dT primer (Applied Biosystems, Branchburg, NJ), and real-time RT-PCR was performed using 7900H Fast Real-Time PCR System (Applied Biosystems), as previously described (19). The set of primers for mouse Reg I, Reg II, Reg III␣, Reg III␤, Reg III␥, Reg III␦, Reg IV, and GAPDH were prepared as shown in Table 2.…”
Section: Animal Model Reg I Ko (Reg Imentioning
confidence: 99%